1998
DOI: 10.1080/14634989808657009
|View full text |Cite
|
Sign up to set email alerts
|

Stress protein accumulation as an indicator of impact by the petroleum industry in Todos os Santos Bay, Brazil

Abstract: The relative concentrations of stress proteins in juvenile mangrove oysters (Crassostrea rhizophorae), from six study sites in Todos os Santos Bay, Bahia, Brazil, were used to evaluate the possibility of chronic environmental impact induced by 40 years of exposure to the local petroleum industry. Replicated tissue samples from oysters at four sites associated with the extraction, transport and refinement of petroleum, and from two control sites, were used for stress protein (60 kDa) determination. The relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Previous studies in the Bay of Todos os Santos (Nascimento, 1996;Tavares, 1996;da Silva et al, 1997;Nascimento et al, 1998bNascimento et al, , 2000a identified a moderate to low pollution potential in all areas of the petroleum industry, except for the refinery site, where the sediment toxicity was classified as high (Nascimento et al, 1998a(Nascimento et al, , 2000a.…”
Section: Article In Pressmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies in the Bay of Todos os Santos (Nascimento, 1996;Tavares, 1996;da Silva et al, 1997;Nascimento et al, 1998bNascimento et al, , 2000a identified a moderate to low pollution potential in all areas of the petroleum industry, except for the refinery site, where the sediment toxicity was classified as high (Nascimento et al, 1998a(Nascimento et al, , 2000a.…”
Section: Article In Pressmentioning
confidence: 97%
“…The use of biomarkers is a promising approach for detecting in situ the early adverse effects of pollutants on organisms (Depledge, 1994;Nascimento et al, 1998b). The primary effect of toxicants is the perturbation of biochemical and molecular processes within the cell, which may alter the life functions of all exposed organisms (Bayne et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Biomarkers involve biological responses to stressors, evaluated at a biochemical, cellular or physiological levels (Nascimento et al 2006). The first ecotoxicological effects resultant from interactions between the pollutant and the biota happen at a biochemical/cellular level (Nascimento et al 1998;Fent 2001). Thus biomarkers can detect cyto-physiological alterations in organisms exposed to contaminants, previously to disease installation and death (Petrovic et al 2004;Martins et al 2005).…”
mentioning
confidence: 99%
“…Except for a few studies on chemical sediment contamination (Tavares, 1986), and others related to the acute impacts of oil spills (CRA, 2000) and ecological surveys carried out between 1994-2000(Peso-Aguiar and Almeida, 1996Nascimento, 1996;Nascimento et al, 1998Nascimento et al, , 2000b, no integrative evaluation of the possible effects has been generated. Todos os Santos bay is bordered by an extensive mangrove ecosystem making the development of environmental diagnosis, techniques and monitoring programs priority for this bay.…”
Section: Advances On Sediment Quality Assessment In Brazil: Case Studiesmentioning
confidence: 99%
“…The use of biomarkers (biological responses to pollutant effects, considered at molecular, sub cellular, cellular, histological and physiological organizational levels) is one of the most promising approaches for detecting in situ the early adverse effects of pollutants on organisms (Depledge, 1994;Nascimento et al, 1998). The lysosomal membrane liability has been indicated as a sensitive biomarker , based on its capacity to respond to chemical exposure, which in turn determines contaminant-induced alterations in cell structure and function (Lowe et al, 1995a).…”
Section: Advances On Sediment Quality Assessment In Brazil: Case Studiesmentioning
confidence: 99%